Ireland : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that Ireland's economic performance in recent years has been exceptionally strong. Output and employment have been growing much faster than in the rest of Europe. Real GDP growth averaged 7.5 percent per year in 1993-98, reflecting a sharp increase in capital accumulation-fueled in part by foreign direct investment-and an expansion of the skilled labor force owing to young entrants, increasing female participation, and a reversal of net emigration. Inflation has remained subdued. Public finances have improved significantly and the external current account has remained in surplus.